On the Limitations of Ludwig Wittgenstein’s Anti-Intellectualist Philosophy - Leunbach, Daniel (Academy of Management Review, 2024)
This dissertation explores how and why some decision-makers manage fundamental uncertainty better than others. Fundamental uncertainty is defined as situations where it is impossible to assign probabilities to a knowable set of outcomes. The dissertation is divided into three parts, each with its own approach to this topic. The first part, based on empirical articles published in the Journal of International Entrepreneurship and the Quarterly Journal of Austrian Economics, examines why some entrepreneurial teams handle uncertainty better than others. The second part critiques effectuation theory, which is a central framework for understanding how entrepreneurs think and act under uncertainty, and develops constructive theoretical alternatives based on the poetry and thought of John Keats (1795-1821), one of the most widely admired poets of the Romantic era. The third part, based on conceptual articles published in the Scandinavian Journal of Management and the Academy of Management Review, examines how uncertainty can be managed at an institutional level. This part uses Wittgenstein's philosophy to argue that a research domain that allows for a moderate degree of conceptual pluralism in the understanding of entrepreneurship will be better equipped to handle an uncertain future. It also discusses the strengths and weaknesses of Wittgenstein's philosophy. Overall, this dissertation enriches the discourse on entrepreneurship and uncertainty through empirical studies and philosophical critique.